Trends in the Transmission of Religious Knowledge on Social Media: A Study of Gus Iqdam’s Official YouTube Channel - Muhammad Arman Al Jufri; Samsul Bahri (Jurnal Komunikasi Islam, 2024)
This study examines Gus Iqdam Official’s YouTube channel as a representation of a new trend in the process of transmitting religious knowledge. This article aims to examine this phenomenon from the perspective of religious mediatization, the factors behind its emergence, and the impact given by the process of transmitting religious knowledge in new media. The findings illustrate that Gus Iqdam Official represents a form of transformation of the role of the media in taking the role of the process of availability of religious knowledge in digital era. This is due to the increased strengthening of the media’s role in the lives of people, which forms a new habitus of accessing religious knowledge. Additionally, the presence of “Gus Iqdam Official” shows that traditional religious authorities can civilize with new media and assert Gus Iqdam’s religious authority.